2014
DOI: 10.3892/ijmm.2014.2037
|View full text |Cite
|
Sign up to set email alerts
|

A peptide from Porphyra yezoensis stimulates the proliferation of IEC-6 cells by activating the insulin-like growth factor I receptor signaling pathway

Abstract: Porphyra yezoensis (P. yezoensis) is the most noteworthy red alga and is mainly consumed in China, Japan and Korea. In the present study, the effects of a P. yezoensis peptide (PY-PE) on cell proliferation and the associated signaling pathways were examined in IEC-6 rat intestinal epithelial cells. First, the MTS assay showed that PY-PE induced cell proliferation in a dose-dependent manner. Subsequently, the mechanism behind the proliferative activity induced by PY-PE was determined. The insulin-like growth fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Food derived bioactive peptides have been shown to modulate intestinal epithelial cell differentiation and cytokine production [ 76 ]. Among these, a bioactive peptide derived from Porphyra yezoensis , termed PY-PE or PYP1, whose sequence is A-L-E-G-G-K-S-S-G-G-G-E-A-T-R-D-P-E-P-T, has been shown to induce the proliferation of IEC-6 cells, a rat intestinal epithelial cell line [ 77 , 78 ]. The stimulation of two different molecular signaling pathways has been found to be involved in this effect.…”
Section: Red Seaweeds and Intestinal Mucosal Barrier Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Food derived bioactive peptides have been shown to modulate intestinal epithelial cell differentiation and cytokine production [ 76 ]. Among these, a bioactive peptide derived from Porphyra yezoensis , termed PY-PE or PYP1, whose sequence is A-L-E-G-G-K-S-S-G-G-G-E-A-T-R-D-P-E-P-T, has been shown to induce the proliferation of IEC-6 cells, a rat intestinal epithelial cell line [ 77 , 78 ]. The stimulation of two different molecular signaling pathways has been found to be involved in this effect.…”
Section: Red Seaweeds and Intestinal Mucosal Barrier Functionmentioning
confidence: 99%
“…Peptide PY-PE also stimulates the expression of type I IGFR, which is involved in the promotion of cell proliferation and the inhibition of apoptosis [ 77 ], and of the adaptor molecules insulin receptor substrate-1 (IRS-1) and Shc. As a result PY-PE stimulates the phophatidylinositol 3-kinase (PI3K)/protein kinase B (PKB or AKT) pathway, ERK, and the expression of AP-1 proteins c-Jun and c-Fos [ 78 ]. Therefore PY-PE induces cell proliferation through the stimulation of different receptor and signal transduction pathways in IEC-6 cells [ 77 , 78 ].…”
Section: Red Seaweeds and Intestinal Mucosal Barrier Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, only one study using a particular PYP peptide has reported its regulation of multiple cell growth-related signals in MCF-7 cells ( 25 ). PYP has also been shown to stimulate the proliferation of IEC-6 normal intestinal epithelial cells and is associated with the insulin-like growth factor I (IGF-IR) and epidermal growth factor receptor (EGFR) signaling pathways ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by our group reported on the cellular and molecular effects of peptide and hydrophilic protein extracts of the brown seaweed Porphyra yezoensis (P. yezoensis) based on analyses of cytotoxicity (20,32), inflammation (33)(34)(35)(36)(37) and cell proliferation (38)(39)(40)(41). However, the biological effects of P. yezoensis protein (PYP) on cisplatin-induced renal injury have remained elusive.…”
Section: Protein Extracted From Porphyra Yezoensis Prevents Cisplatinmentioning
confidence: 99%